2018
DOI: 10.1002/cbin.10951
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PPARG on AGEs‐induced AKT/MTOR signaling‐associated human chondrocytes autophagy

Abstract: Accumulation of advanced glycation end products (AGEs) in articular cartilage is thought to represent a major risk factor for osteoarthritis development. In this study we aimed to probe the role of AGEs in human chondrocytes and to determine the impact of the peroxisome proliferator-activated receptor-γ (PPARG) on AGEs-induced cell autophagy. Cell viability was measured after human chondrocytes were treated with different concentrations of AGEs with or without the PPARG inhibitor, T0070907, or agonist, pioglit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 28 publications
(46 reference statements)
2
31
0
Order By: Relevance
“…In addition, 5Aza significantly alleviated the abnormal expression of Adamts5, MMP13, Collagen2 and Aggrecan in IL-1β-treated chondrocytes (figure 4B). Intriguingly, the beneficial effects were largely abolished in presence of a specific PPARγ inhibitor T007090736 (figure 4C,D), suggesting that 5Aza restoration of PPARγ contributes significantly to the chondro-protective effects.…”
Section: Resultsmentioning
confidence: 93%
“…In addition, 5Aza significantly alleviated the abnormal expression of Adamts5, MMP13, Collagen2 and Aggrecan in IL-1β-treated chondrocytes (figure 4B). Intriguingly, the beneficial effects were largely abolished in presence of a specific PPARγ inhibitor T007090736 (figure 4C,D), suggesting that 5Aza restoration of PPARγ contributes significantly to the chondro-protective effects.…”
Section: Resultsmentioning
confidence: 93%
“…For group (5), 3-MA was added into the lower chambers for 24 h. All experiments were performed in triplicate. The concentration of AGEs (200 μ g/ml) and 3-MA (2 mM) used in the present study was referred to previous studies [3335].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it has been demonstrated that canonical PI3Kγ signaling in myeloid cells is essential to restrict T. cruzi heart parasitism and ultimately to avoid myocarditis, heart damage, and death in mice (23). Furthermore, in a human in vitro model of osteoarthritis characterized by increased advanced glycation end (AGE) products accumulation and reduced autophagy, it was demonstrated that pioglitazone, a PPARγ ligand, increased AKT/mTOR phosphorylation in a dose-dependent manner, leading to better cell viability and inducing increased chondrocyte autophagy (43). However, several works on cancer and neurodegenerative diseases have shown that PPARγ activation inhibits the PI3K/AKT/mTOR signaling pathway (44)(45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%